Heat Shock Proteins and Cancer. (March 2017) - Wu, Jianming; Liu, Tuoen; Rios, Zechary; Mei, Qibing; Lin, Xiukun; Cao, Shousong
Abstract : Heat shock proteins (HSPs) constitute a large family of proteins involved in protein folding and maturation whose expression is induced by heat shock or other stressors. The major groups are classified based on their molecular weights and include HSP27, HSP40, HSP60, HSP70, HSP90, and large HSPs.HSPs play a significant role in cellular proliferation, differentiation, and carcinogenesis. In this article we comprehensively review the roles of major HSPs in cancer biology and pharmacology. HSPs are thought to play significant roles in the molecular mechanisms leading to cancer development and metastasis. HSPs may also have potential clinical uses as biomarkers for cancer diagnosis, for assessing disease progression, or as therapeutic targets for cancer therapy. Trends: HSPs are molecular chaperones which facilitate protein folding and maintain protein structure and function during stress. HSPs are classified mainly based on their molecular weight. HSPs play important roles in carcinogenesis via the regulation of angiogenesis, cell proliferation, migration, invasion, and metastasis. HSPs also mediate apoptosis and resistance to some anticancer drugs. In addition, HSPs have potential clinical use as biomarkers for cancer diagnosis and prognosis, as well as therapeutic targets. The HSP70 and HSP90 classes of HSPs have been the most widely studied given their important roles in cancer. HSP90 inhibitors have been investigated in preclinical and clinical trials as novel anticancer agents. Large HSPs are used in vaccines for cancer immunotherapy. In addition to conventional chemotherapeutic drugs targeting HSPs, other inhibitors of HSPs such as antibodies, natural compounds, peptides, and vaccines have been developed. Different HSP family members collaborate with each other in a signaling network to regulate cellular functions. A combination of different HSP inhibitors may therefore enhance anticancer efficacy.